Typology of Structural Relations for Information Analysis and Consolidation Processes - Gopinath, M. A. (Journal of Information and Knowledge, 1992)
Defines the information analysis and consolidation processes. Discusses the static and dynamic aspects of organisation of information. Presents a typology of relations for structural relations and for consolidation processes.